The London Passenger Transport Act of 1933: A New Socialization - Plummer, Alfred (Quarterly Journal of Economics, 1933)
Journal Article The London Passenger Transport Act of 1933: A New Socialization Get access Alfred Plummer Alfred Plummer Ruskin College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 48, Issue 1, November 1933, Pages 181–193, https://doi.org/10.2307/1884802 Published: 01 November 1933